DIFFERENT APPROACHES TO THE QUANTITATIVE-STATISTICAL CHARACTERISTICS OF PARTS OF SPEECH IN THE ENGLISH LANGUAGE - Abdullayev, Ikramjon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article explores different approaches to the quantitative-statistical characteristics of parts of speech in the English language. Parts of speech, including collocations, phrases, and syntactic constructions, play a fundamental role in language structure and usage. By employing quantitative-statistical analysis, researchers can investigate various aspects of parts of speech, such as frequency, distribution, collocational patterns, semantic associations, and syntactic properties. This analysis provides valuable insights into language phenomena, including lexical semantics, syntactic structures, discourse coherence, language variation, and language change. Furthermore, quantitative-statistical techniques contribute to natural language processing tasks, such as information retrieval, sentiment analysis, named entity recognition, and machine translation. The article discusses several applications and implications of quantitative-statistical analysis in the study of parts of speech, highlighting its importance in understanding and modeling the English language.